Riqueza, abundância e composição de mariposas noturnas Lepidoptera (Sphingidae e Saturniidae) em uma floresta estacional decidual - Viana, Guilherme Magalhães (2020)
The loss of tropical forests and their biodiversity due to human actions that occur over several years, are giving opportunity to secondary forests. Secondary forests are considered a repository of biodiversity, being the environment that will obtain greater diversity in the anthropocene. the moths of the families Sphingidae and Saturniidae are very dependent on vegetation, being considered pests in larval stages, pollinators in adulthood. Due to the ecological importance that these two families present, this dissertation aimed to make the first survey of the families Sphingidae and Saturniidae in a seasonal deciduous forest; verify if the monthly rainfall has a relationship with the abundance and richness of sphingids and saturnids; test whether the floristic composition (conserved forest versus secondary forest) will influence the moth community. The work was carried out at Pau Furado State Park, the predominant phytophysiognomy is the deciduous seasonal forest. These forests are in two different successional stages "conserved forests" and "secondary forests". A total of 78 individuals were found, of 22 species of sphinxes, the observed richness is like the Caatinga richness. A new record has been found for the Cerrado. In the survey of saturnids, 45 species and 874 individuals were found. The abundance and wealth were higher than other work in dry forests outside Brazil, but when compared to surveys in the Cerrado, it showed a low abundance and wealth. The monthly rainfall did not influence the wealth and abundance of the two families. The floristic community influenced the moth community, having a positive correlation with the moths. The influence of vegetation on the moth community, can be explained by the specificity of the immature with its host plant, with this, we confirm again the high dependence of the community of Sphingidae and Saturniidae with the nearby vegetation.